One Step Forward toward Characterization: Some Important Material Properties to Distinguish Biochars - Schimmelpfennig, Sonja; Glaser, Bruno (Journal of environmental quality, 2012)
Terra Preta research gave evidence for the positive influence of charred organic material (biochar) on infertile tropical soils. Facing global challenges such as land degradation, fossil energy decline, water shortage, and climate change, the use of biochar as a soil amendment embedded into regional matter cycles seems to provide an all‐round solution. However, little is known about biochar effects on individual ecosystem processes. Besides, the term biochar is used for a variety of charred products. Therefore, the aim of this study was to investigate principal material properties of different chars to establish a minimum set of analytical properties and thresholds for biochar identification. For this purpose, chars from different production processes (traditional charcoal stack, rotary kiln, Pyreg reactor, wood gasifier, and hydrothermal carbonization) were analyzed for physical and chemical properties such as surface area, black carbon, polycyclic aromatic hydrocarbons, and elemental composition. Our results showed a significant influence of production processes on biochar properties. Based on our results, to identify biochar suitable for soil amendment and carbon sequestration, we recommend using variables with the following thresholds: O/C ratio <0.4, H/C ratio <0.6, black carbon >15% C, polyaromatic hydrocarbons lower than soil background values, and a surface area >100 m2 g−1.